Medieval markets: A soil micromorphological and archaeobotanical study of the urban stratigraphy of Lier (Belgium). (1st December 2017) - Wouters, Barbora; Devos, Yannick; Milek, Karen; Vrydaghs, Luc; Bartholomieux, Bart; Tys, Dries; Moolhuizen, Cornelie; van Asch, Nelleke
Abstract: Market places remain underrepresented in studies of archaeological soil micromorphology. In Lier, micromorphology was applied to gain understanding of the stratigraphy and formation processes of the medieval "Grote Markt". Block samples were obtained from a sediment profile that spanned the 11 th -15th century and contained three separate phases of thick, dark-coloured, humic, homogeneous layers - so-called 'dark earth'. Combined with textural and archaeobotanical analyses (seeds, fruits and phytoliths), the results shed light on the formation processes that shaped this site. The oldest dark earth, dated to the 11th century, was characterised by agricultural activities. The second dark earth (12–13th century) formed as a result of intensive human activities, witnessing the site's transformation to an urban space. This layer contained large amounts of organic matter and anthropogenic inclusions and developed gradually in situ . It probably represents an early market or open space close to dwellings or small courtyards. Units that contain evidence for intensive building activity separate the second and third dark earth, and are possibly the result of a spatial re-organisation of the square. The formation of the third dark earth, which started in the 14th century, is characterised by an intensification of traffic and craftworking activities. Surfaces may have been maintained by spreading organic matter such as leaves, sand and hearth detritus. However, there is no evidence for a kept, empty urban square before a thick layer of levelling sand was deposited (in the second half of the 14th century at earliest) and the market was cobbled. The analysis shows that mixed market activities took place in this intensively used zone, and presents a number of micromorphological characteristics and inclusions typical of a medieval market place in a temperate climate.